Eutrophication causes, consequences and control - Ansari, Abid A. (Springer, 2011)
Eutrophication continues to be a major global challenge to water quality scientists. The global demand on water resources due to population increases, economic development, and emerging energy development schemes has created new environmental challenges to global sustainability. Eutrophication, causes, consequences, and control provides a current account of many important aspects of the processes of natural and accelerated eutrophication in major aquatic ecosystems around the world. The connections between accelerated eutrophication and climate change, chemical contamination of surface waters, and major environmental and ecological impacts on aquatic ecosystems are discussed. Water quality changes typical of eutrophication events in major climate zones including temperate, tropical, subtropical, and arid regions are included along with current approaches to treat and control increased eutrophication around the world. The book provides many useful new insights to address the challenges of global increases in eutrophication and the increasing threats to biodiversity and water quality.